Intergenerational Food Insecurity, Underlying Factors, and Opportunities for Intervention in Momostenango, Guatemala. (14th June 2022) - Lane, Ginny; Cordon, Karla; Monroy-Valle, Michele; Vatanparast, Hassan; Xinico, Silvia
Abstract: Objectives: Identify the impacts of climate changes on food production, community food security and household food security in rural Momostenango, Guatemala. Methods: Cross sectional mixed methods study involving in-depth interviews with 12 agricultural group leaders in six communities and surveys with 55 mothers in 13 distinct communities. Food secure and food insecure households were compared using chi squared tests. Results: Key informant interview themes were subsistence agriculture; commercial production; climate, capital, market, and capacity challenges; and sustainable opportunities. Eighty-five % of interviewed households were food insecure. The vast majority of households (93%) were engaged in agriculture, with food secure families working their own or leased land, while food insecure families worked their own land in addition to engaging in day labor. During seasonal periods of food scarcity, families reported altering food use, reducing expenses, and generating funds. Severely food insecure families were significantly more likely to reduce portion sizes (72%), while food secure families only ate less preferred foods. Reduced intake of beans - a primary protein source - was only reported by some severely food insecure households (22%). Overall, food insecure households are characterized by being larger, having an older mother with less education due to economic restraints during childhood, and deriving most family income from agricultural day labor. Community members indicated interest in establishing small-scale home-based interventions such as hen and egg operations and trying high protein or climate-adapted corn to enhance food security. Conclusions: Severely food insecure families consumed a less diverse diet, smaller portions, and reduced bean intake (key protein source) during periods of food scarcity; while moderately food insecure families consumed a less diverse diet and smaller portions; and food secure families only ate less preferred foods. Food insecurity in rural Guatemala is a long-term structural phenomenon associated with limited family resources that reproduces itself in subsequent generations. Funding Sources: Queen Elizabeth Scholars through Universities Canada.